Stabilization of warfarin‐binding pocket of VKORC1 and VKORL1 by a peripheral region determines their different sensitivity to warfarin inhibition. (20th May 2018) - Shen, G.; Li, S.; Cui, W.; Liu, S.; Liu, Q.; Yang, Y.; Gross, M.; Li, W.
Summary: Essentials VKORL1 and VKORC1 have a similar overall structure and warfarin‐binding pocket. A peripheral region stabilizing this pocket controls warfarin sensitivity of the VKOR paralogs. A human single nucleotide polymorphism in this region renders VKORL1 sensitive to warfarin. A group of warfarin‐resistant mutations in VKORC1 acts by disrupting peripheral interactions. Summary: Background: The human genome encodes two paralogs of vitamin‐K‐epoxide reductase, VKORC1 and VKORL1, that support blood coagulation and other vitamin‐K‐dependent processes. Warfarin inhibits both enzymes, but VKORL1 is relatively resistant to warfarin. Objectives: To understand the difference between VKORL1 and VKORC1, and the cause of warfarin‐resistant (WR) mutations in VKORC1. Methods: We performed systematic mutagenesis and analyzed warfarin responses with a cell‐based activity assay. Mass spectrometry analyses were used to detect cellular redox state. Results: VKORC1 and VKORL1 adopt a similar intracellular redox state with four‐transmembrane‐helix topology. Most WR mutations identified in VKORC1 also confer resistance in VKORL1, indicating that warfarin inhibits these paralogs at a common binding site. A group of WR mutations, distant from the warfarin‐binding site, show significantly less resistance in VKORL1 than in VKORC1, implying that their different warfarin responses are determined by peripheral interactions. Remarkably, we identify a critical peripheral region in which single mutations, Glu37Lys or His46Tyr, drastically increase the warfarin sensitivity of VKORL1. In the background of these warfarin‐sensitive VKORL1 mutants, WR mutations showing relative less resistance in wild‐type VKORL1 become much more resistant, suggesting a structural conversion to resemble VKORC1. At this peripheral region, we also identified a human single nucleotide polymorphism that confers warfarin sensitivity of VKORL1. Conclusions: Peripheral regions of VKORC1 and VKORL1 primarily maintain the stability of their common warfarin‐binding pocket, and differences of such interactions determine their relative sensitivity to warfarin inhibition. This new model also explains most WR mutations located at the peripheral regions of VKORC1.